Anticipated changes in human resource management: views from the field. - Hays, Steven W.; Kearney, Richard C. (Public Administration Review)
This article reports the results of a major survey that was distributed to the members of the International Personnel Management Association and the Section on Personnel and Labor Relations of the American Society for Public Administration. The intent of the survey was twofold: to gauge the respondents' perspectives on the relative importance of various personnel techniques, activities, and values, and to assess their projections concerning the changes that will occur during the next decade. In addition to providing an interesting snapshot of the perceived state of modernization within public-sector human resource management, the results reflect a considerable degree of agreement concerning the expected direction of further changes. Themes arising from the reinvention movement, as well as the technological revolution, dominate the response patterns. The implications of these perceived alterations in the field of human resource management are discussed, and potential problem areas are identified. Reprinted by permission of the publisher.